Development of date pit–polystyrene thermoplastic heat insulator material: Mechanical properties. (April 2021) - Hittini, Waseem; Abu-Jdayil, Basim; Mourad, Abdel-Hamid
In this work, an investigation of the mechanical behavior of thermoplastic polystyrene (PS) composites containing date pit powder (DPP) is presented. DPP waste contents ranging from 0 wt% to 50 wt% were used to prepare the PS composite. The experimental results revealed that the addition of DPP to the PS matrix decreased the compressive, tensile, and flexural strengths and moduli of the composite. The reduction in the composite's compressive strength was minimal with filler contents up to 30%. The DPP-PS composites demonstrated superior tensile strength (1.12–0.34 MPa), compressive strength (11.58–2.31 MPa), and flexural strength (21.10–2.37 MPa) when compared with the commonly used insulating materials and comparable to some construction materials. The negative impact of DPP on the mechanical properties of PS was attributed to the agglomeration of the natural fillers creating stress concentration points, as well as poor compatibility between the fillers and the PS matrix. Alkaline treatment of DPP with sodium hydroxide solution enhanced marginally the compressive strength (by 4.2%) and effectively the tensile (by 190%) and flexural strength (by 55%) of all prepared composites. The scanning electron microscopy micrographs demonstrated that the treatment effectively changed the surface roughness of the date pit particles and enhanced the interference between the fillers and the PS matrix. Thermogravimetric analysis and Fourier transform infrared spectra of the treated filler indicate that the observed improvement in adhesion was due to removal of hydrophilic components from DPP.